Black tea enhances alertness fifteen minutes after consumption - Dinesh Syce (Asian Journal of Medical Sciences)
Background: Although there is an abundance of research regarding the enhancement of psychomotor function following the ingestion of coffee and pure caffeine, the actions of black tea on the reaction time and other tests of psychomotor function have not been researched as extensively.